Pengaruh Latihan Mirror Therapy Terhadap Kemampuan Fungsional Upper Extremity Pada Pasien Post Stroke - Falaah, Nuur; Kurniawan, Ganesa Puput Dinda; Agustina, Dwi; Abida, Liza Laela; Laksono, Abdurahman Berbudi Bowo (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Bacground: Non-communicable diseases like stroke are on the rise in Indonesia and are a leading cause of disability. Stroke often results in upper extremity dysfunction, affecting daily independence. One emerging physiotherapy intervention in stroke rehabilitation is mirror therapy, which uses visual stimulation with mirrors to improve motor function.Objective: To determine the effect of mirror therapy exercises on improving upper extremity functional ability in post-stroke patients. Methods: This study employed a pre-experimental one-group pretest-posttest design. A total of 11 samples were selected using purposive sampling. The independent variable was mirror therapy exercises, and the functional ability of the upper extremity was measured using the CAHAI-9. Data were analyzed for normality using the Shapiro-Wilk test, and hypothesis testing was conducted using the Paired Sample T Test. Results: The mean upper extremity functional score before the intervention was 29.36, and increased to 32.45 after the intervention, with a p-value of 0.00 (p < 0.05). Conclusion: Mirror therapy exercises have a significant effect on improving upper extremity functional ability in post-stroke patients. Suggestion : This exercise may serve as an effective physiotherapy intervention to enhance upper limb function in individuals recovering from stroke.